APPROACHES TO ENSURING RESOURCE EFFICIENCY IN THE PRODUCTION OF PAPER AND CARDBOARD (REVIEW) - MUKALO, YEVHENII; HALYSH, VITA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Nowadays, Ukraine has chosen the European vector as the direction of its development. That is why industrial development must take into account the principles and norms of sustainable development and the circular economy. Ensuring resource efficiency is a necessary condition for the development of any enterprise. Due to economic and environmental restrictions, production of cardboard and paper products is being improved towards the use of waste paper, which leads to pollution of wastewater, and increased use of fresh water. An important problem in the use of waste paper is its polydispersity, which consists in the use of various cellulose fibers and fillers in the production of cardboard and paper products. Such polydispersity has a significant impact on the quality of the finished product and on wastewater pollution. The problem of effective treatment of industrial wastewater from paper production to obtain water for repeated use in the technological process, as well as the urgent problem of processing secondary waste from wastewater treatment remain unresolved. The issue of paper production development in the context of sustainable development should be developed taking into account technical and technological achievements in the field of ecology and chemical technology to ensure the efficient use of raw materials, in particular water and fibrous semi-finished products. The main problems associated with the use of secondary raw materials are described, taking into account environmental and economic aspects. Technological approaches, which allow to ensure the sustainable development of the industry, are described and analyzed. In general, the successful experience of European manufacturers in creating resource-efficient and clean technologies can be used as the basis for the further development of domestic enterprises.
Keywords: waste paper; wastewater; cardboard; sustainability; treatment